Разложите на множители квадратный трёхчлен:(х2 - в квадрате)

а) х2 + 5х - 14

б)16х2 - 14х + 3

Сократить дробь: 3у2 - 7у -6 (ЭТО ДРОБЬ)

4-9у2

2

Ответы и объяснения

2012-11-01T16:39:11+04:00

а) х2 + 5х - 14=(x+7)*(x-2)

x1 = -7, x2 = 2

б)16х2 - 14х + 3=(x-0,375)*(x-0,5)

x1 = 0,375, x2 = 0,5

в)

 3у2 - 7у -6 =  (3y+2)*(y-3)  =  y-3

    4-9у2         (2-3y)*(2+3y)    2-3y

1)3у2 - 7у -6=3*(y+2/3)*(y-3)=(3y+2)*(y-3)

y1 =-2/3, y2 = 3

2) 4-9у2=(2-3y)*(2+3y)

2012-11-01T16:39:31+04:00

а) х2+5х-14=(х-2)(х+7);

х2+5х-14=0;

Д=25-4*(-14)=25+56=81;

х1=(-5+9)/2=4/2=2;

х2=(-5-9)/2=-14/2=-7;

б)16х2-14х+3=16(х-0,5)(х-0,375);

16х2-14х+3=0

Д=(-14)2-4*16*3=196-192=4;

х1=(14+2)/32=16/32=0,5;

х2=(14-2)/32=12/32=0,375;

в)(3у2-7у-6)/(4-9у2)=3(у-3)(у+2/3)/-9(у-2/3)(у+2/3)=3(у-3)/(6-9у)=

(3у-9)/(6-9у)=3(у-3)/3(2-3у)=(у-3)/(2-3у);

3у2-7у-6=(у-3)(у+2/3);

3у2-7у-6=0

Д=49-4*3*(-6)=49+72=121;

у1=(7+11)/6=18/6=3;

у2=(7-11)/6=-4/6=-2/3;

4-9у2=-9(у-2/3)(у+2/3);

4-9у2=0

9у2=4

у1=4/9=2/3;

у2=-2/3.